Analisis Pemakaian Daya Listrik Genset Berbasis Ekonomi Teknik PT. Teladan Kutai Timur - Dyah Andini Puspasari; Qomaruddin; H. Masing (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2025)
Electricity has become an essential need in daily life and is a primary resource that supports various economic activities. Along with the growth of the population, technological advancements, and increased investments, the demand for electricity supply is projected to continue rising. In Indonesia, PLN (Perusahaan Listrik Negara) is the main electricity provider, but it often faces challenges in meeting this demand, especially with frequent power outages that disrupt industrial and societal activities. To address this issue, many companies have turned to using generator sets (gensets) as an alternative solution to ensure a stable energy supply. Although the use of gensets provides energy independence, it requires a significant investment. Therefore, an in-depth analysis of the efficiency and economic feasibility of using gensets is necessary. This study aims to analyze the use of gensets at PT. Teladan Prima Agro Bukit Permata Mill, located in Kaubun, East Kutai, focusing on technical-economic aspects such as Present Value (PV), Future Value (FV), Net Present Value (NPV), Internal Rate of Return (IRR), and Break Even Point (BEP). Data collected directly from the field includes genset specifications, electricity load, energy consumption, fuel usage, and genset operations. The analysis results indicate that the 455 KVA genset is capable of meeting the factory's electricity needs with an initial cost of IDR 649,649,996. The NPV calculation shows a value of IDR 880,380,813, with an IRR of 6.63%. The BEP is achieved in the 12th month with a profit of IDR 109,645,114. Based on these results, the operation of the genset at PT. Teladan Prima Agro Bukit Permata Mill is considered feasible and profitable in the long term.